Involvement of Cholesterol Metabolic Pathways in Recovery from Noise-Induced Hearing Loss - Na Sai; Xi Shi; Yan Zhang; Qing-qing Jiang; Fei Ji; Shuo-long Yuan; Wei Sun; Wei-Wei Guo; Shi-Ming Yang; Wei-Ju Han (Neural Plasticity)
The objective of this study was to explore the molecular mechanisms of acute noise-induced hearing loss and recovery of steady-state noise-induced hearing loss using miniature pigs. We used miniature pigs exposed to white noise at 120 dB (A) as a model. Auditory brainstem response (ABR) measurements were made before noise exposure, 1 day and 7 days after noise exposure. Proteomic Isobaric Tags for Relative and Absolute Quantification (iTRAQ) was used to observe changes in proteins of the miniature pig inner ear following noise exposure. Western blot and immunofluorescence were performed for further quantitative and qualitative analysis of proteomic changes. The average ABR-click threshold of miniature pigs before noise exposure, 1 day and 7 days after noise exposure, were 39.4 dB SPL, 67.1 dB SPL, and 50.8 dB SPL, respectively. In total, 2,158 proteins were identified using iTRAQ. Both gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) database analyses showed that immune and metabolic pathways were prominently involved during the impairment stage of acute hearing loss. During the recovery stage of acute hearing loss, most differentially expressed proteins were related to cholesterol metabolism. Western blot and immunofluorescence showed accumulation of reactive oxygen species and nuclear translocation of NF-κB (p65) in the hair cells of miniature pig inner ears during the acute hearing loss stage after noise exposure. Nuclear translocation of NF-κB (p65) may be associated with overexpression of downstream inflammatory factors. Apolipoprotein (Apo) A1 and Apo E were significantly upregulated during the recovery stage of hearing loss and may be related to activation of cholesterol metabolic pathways. This is the first study to use proteomics analysis to analyze the molecular mechanisms of acute noise-induced hearing loss and its recovery in a large animal model (miniature pigs). Our results showed that activation of metabolic, inflammatory, and innate immunity pathways may be involved in acute noise-induced hearing loss, while cholesterol metabolic pathways may play an important role in recovery of hearing ability following noise-induced hearing loss.